Comparison of microwave assisted acid digestion methods for ICP-MS determination of total arsenic in fish tissue - Ghanthimathi .S,; Aminah .A,; Salmijah .S,; Ujang .T,; Nurul Izzah .A, (Universiti Kebangsaan Malaysia, 2012)
Fish is one of the most important sources of arsenic exposure in human diet and the Food Safety and Quality Division, Ministry of Health since 2007 has required routine monitoring of total arsenic in seafoods such as fish. This study describes an improved extraction method of total arsenic in fish using microwave assisted acid digestion procedure before being analysed by inductively coupled plasma mass spectrometry (ICP-MS). The parameters studied were pre-treatment of sample, digestion temperature, time programme and the chemicals (HNO3/H2O2) used. Arsenic contents in fish samples under these conditions were compared using the standards additions technique. Microwave assisted acid digestion method with a combination of ultrapure concentrated nitric acid (HNO3) to concentrated hydrogen peroxide (H2O2) at a ratio of 7 mL: 1 mL, run time of 25 min and digestion temperature of 200°C with no pre-treatment was found to have recovery of 100.7% as compared with other digestion procedure where the recovery were 115.5, 111.6 and 101.8%. Validation using certified reference material (CRM) of fish tissue (DORM-3) showed a recovery of 101.4 ± 2.5% for total arsenic from the CRM.